2019
DOI: 10.7759/cureus.5531
|View full text |Cite
|
Sign up to set email alerts
|

Complete Remission of Bone Metastases in Renal Cell Carcinoma with Nivolumab

Abstract: A 60-year-old female, who presented with abdominal discomfort, was noted to have an enhancing left renal mass, with central necrosis on a CT scan. She underwent radical nephrectomy and biopsy revealed clear cell renal cell carcinoma, Fuhrman grade 4. After 1.5 years of her surgery, she developed metastatic disease with pulmonary nodules and was started on sunitinib. She had disease progression with development of a new 8.2 x 7.6 cm expansile, lytic bony lesion with a complete destruction of the left scapula an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
(10 reference statements)
0
9
0
Order By: Relevance
“…In both cases, nivolumab, which was introduced as a second-line treatment after the molecular-targeted drug, improved bone metastases. Vuyyala et al (17) reported that a solitary scapular metastasis with osteolytic change was remodeled with osteosclerotic change by nivolumab treatment without the concomitant use of a bone-modifying agent (BMA). Marsh et al (18) reported that the accumulation of a solitary thoracic vertebral body on positron emission tomography (PET) disappeared after nivolumab treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In both cases, nivolumab, which was introduced as a second-line treatment after the molecular-targeted drug, improved bone metastases. Vuyyala et al (17) reported that a solitary scapular metastasis with osteolytic change was remodeled with osteosclerotic change by nivolumab treatment without the concomitant use of a bone-modifying agent (BMA). Marsh et al (18) reported that the accumulation of a solitary thoracic vertebral body on positron emission tomography (PET) disappeared after nivolumab treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Two case reports have shown that bone metastases from RCC were significantly improved by ICI treatment ( 17 , 18 ). In both cases, nivolumab, which was introduced as a second-line treatment after the molecular-targeted drug, improved bone metastases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of ICI on the bone metastases of RCC is not clear. There is a case report that nivolumab monotherapy relieved bone metastases in a metastatic RCC patient who underwent radical nephrectomy [ 142 ]. Negishi et al found that ICI monotherapy had limited effects on bone metastases, which may be related to the decrease of PD-L1 expression in bone metastases, while controlled bone metastases and reduced incidence of skeletal-related events emerged when using radiotherapy combined with ICI [ 143 , 144 ].…”
Section: Clinical Effects Of Immune Checkpoint Inhibitors To Bone Metastasismentioning
confidence: 99%
“…Almost half of the patients with clear cell renal cell carcinoma (ccRCC) develop metastases [1]. Even after surgical treatment of early non-metastatic kidney cancer, metastases occur in 5-15% of cases within five years of follow-up, which significantly affect the survival of patients [2].…”
Section: Introductionmentioning
confidence: 99%